House prices, lending standards, and the macroeconomy - Aino Silvo (Bank of Finland, 2017)
I study the link between house prices, lending standards, and aggregate over-investment in housing. I develop a model of the housing market where the credit market is affected by asymmetric information. Selection is towards less creditworthy borrowers. Asymmetric information coupled with deadweight costs of default can create endogenous boom-bust cycles in house prices. I show that lending standards are loose and the incentives for less-than-creditworthy borrowers to apply for a loan are particularly strong, first, when future house values are expected to be high, which leads to high leverage of borrowers; and second, when safe interest rates are low, which implies low costs of borrowing. However, there are strong nonlinearities in the relationship between borrowing incentives and economic fundamentals. The results shed light on incentive mechanisms that can help explain the developments in the U.S. housing market in the early 2000s. They also imply that loose monetary policy can have a direct impact on the stability of the housing market through the cost of borrowing and the opportunity cost of housing investment.
URN:NBN:fi:bof-201701261058
Keywords: E21; E32; E44; G14; G21; 330